The Oil Drop Experiment: How Did Millikan Decide What Was an Appropriate Drop? - Niaz, Mansoor (Alberta Journal of Educational Research, 2003)
The oil drop experiment is considered an important contribution to the understanding of modern physics and chemistry. The objective of this investigation is to study and contrast the views and understanding with respect to the experiment of physicists or philosophers of science with those of authors of physics or chemistry textbooks and laboratory manuals. Results obtained show that physicists and philosophers of science do understand that the experiment is difficult to perform even today, primarily because of the difficulty associated with the selection of the appropriate drops and that consensus was achieved in the scientific community after a bitter dispute between R.A. Millikan and F. Ehrenhaft. In contrast, authors of physics and chemistry textbooks and laboratory manuals ignore the controversy (especially with respect to the selection of the drops) and present an inductivist interpretation in which empirical data were crucial in the quantization of the charge of the electron. By highlighting the difference between the methodologies of Millikan and Ehrenhaft, textbooks can facilitate students' conceptual understanding of the experiment and thus stimulate interest. It is concluded that although experimental data are important, epistemologically their interpretation through conflicts and controversies is even more important.